2012
DOI: 10.1016/j.bbrc.2012.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced human islet cell death in vitro correlates with a persistently high phosphorylation of STAT-1, but not with NF-κB activation

Abstract: "Cytokine-induced human islet cell death in vitro correlateswith a persistently high phosphorylation of STAT-1, but not with Access to the published version may require subscription. ABSTRACTStudies of insulin producing -cells have reported conflicting responses to NF-κB activation, encompassing both pro-and anti-apoptotic effects, possibly reflecting the use of -cells from different species. Therefore, the aim of this study was to compare the temporal activation of NF-κB in rat and human insulin producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(32 reference statements)
3
10
0
Order By: Relevance
“…The vulnerability of EndoC-βH1 beta cells towards proinflammatory cytokines could be significantly enhanced by a three-dimensional configuration of EndoC-βH1 beta cells as pseudoislets, which can be attributed to improved cell-cell contact. Our results in EndoC-βH1 beta cells are in line with previous observations in human islets [20,[22][23][24].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The vulnerability of EndoC-βH1 beta cells towards proinflammatory cytokines could be significantly enhanced by a three-dimensional configuration of EndoC-βH1 beta cells as pseudoislets, which can be attributed to improved cell-cell contact. Our results in EndoC-βH1 beta cells are in line with previous observations in human islets [20,[22][23][24].…”
Section: Discussionsupporting
confidence: 83%
“…This NFκB activation was primarily dependent on IL-1β, which is in line with a corresponding observation in human islets [24]. The weak cytokine-mediated activation of NFκB in EndoC-βH1 beta cells, as in human islets, failed to induce the iNOS pathway [22,24,33], which is at variance to rodent beta cells [7,13,19,21,[34][35][36][37][38][39]. Our results confirm recent studies in EndoC-βH1 beta cells that reported virtually no expression of iNOS [4,40].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Islets (500) were treated with either vehicle (DMSO, 1 L/mL) alone or with IL-1␤ (100 U/mL) ϩ IFN␥ (300 U/mL) and cultured for up to 48 hours. Because of limited availability of human islets, our studies were confined to testing a combination of proinflammatory cytokines (IL-1␤ϩIFN␥, designated CTK) that has previously been shown to be sufficient in impacting human islet ␤-cell function/survival and promoting insulitis in T1D (25)(26)(27)(28)(29)(30). In some experiments, the islets were pretreated with inhibitors of iPLA 2 ␤ (S-BEL, 10 mol/L) for 30 minutes or NSMase2 (GW4869, 20 mol/L) for 1 hour, prior to treatment with DMSO or CTK.…”
Section: Methodsmentioning
confidence: 99%